2023
DOI: 10.5194/acp-23-15181-2023
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of Southern Ocean atmospheric dimethyl sulfide (DMS) to modeled oceanic DMS concentrations and emissions

Yusuf A. Bhatti,
Laura E. Revell,
Alex J. Schuddeboom
et al.

Abstract: Abstract. The biogeochemical formation of dimethyl sulfide (DMS) from the Southern Ocean is complex, dynamic, and driven by physical, chemical, and biological processes. Such processes, produced by marine biogenic activity, are the dominant source of sulfate aerosol over the Southern Ocean. Using an atmosphere-only configuration of the United Kingdom Earth System Model (UKESM1-AMIP), we performed eight 10-year simulations for the recent past (2009–2018) during austral summer. We tested the sensitivity of atmos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 91 publications
(166 reference statements)
0
4
0
Order By: Relevance
“…A. Bhatti et al (2023) identified a 171% spread in DJF atmospheric DMS from Southern Ocean DMS concentrations and emissions, whereas the spread identified from the simulations performed here during the same period and region is 48%. Although the emissions and concentrations drive much of the spatial and seasonal variability of atmospheric DMS, we demonstrate that differences in CMIP6 chemistry also have a profound influence on Southern Ocean atmospheric DMS.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…A. Bhatti et al (2023) identified a 171% spread in DJF atmospheric DMS from Southern Ocean DMS concentrations and emissions, whereas the spread identified from the simulations performed here during the same period and region is 48%. Although the emissions and concentrations drive much of the spatial and seasonal variability of atmospheric DMS, we demonstrate that differences in CMIP6 chemistry also have a profound influence on Southern Ocean atmospheric DMS.…”
Section: Resultsmentioning
confidence: 62%
“…A. Bhatti et al, 2023), we demonstrate the importance of choosing a sulfate chemical reaction scheme appropriately over the Southern Ocean. As a result, we investigate the global differences in chemical oxidation of DMS between each simulation.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations